Design and implementation of capacitor array as DC converters for electrical lighting in limited area - Arman Jaya; Irianto Irianto; Afif Aulia Rahman; Kyungmin Sung (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2023)
The widely used DC-DC converters are inductor-based DC-DC converters and inductors along with combustion. The use of inductors can lead to large power losses, as well as heavy components in real terms. The proposed converter warning array aims to increase the voltage with a large increase ratio through a switching configuration process. This switching method is very simple and uses two pulses that are opposite each other so that the array converter can work optimally, whose function is to adjust the arrangement in a parallel arrangement to a series arrangement. The advantage of using a device is that it makes DC-based DC conversion lightweight and easy to implement. Tests have been carried out on 5 hanger arrays with a power of 80 W and 65 W, and the data from the test results show that the voltage increase ratio reaches 81.5Â % or 4.08 times the input voltage, which indicates that the array converter warning is able to increase the input voltage according to the number of the arrays.